The Use of Endoscopic Ultrasonography and Other Imaging Modalities in the Preoperative Staging of Rectal Villous Tumours: A Case of Overstaging by Magnetic Resonance Imaging - Michelle Buresi; Iman Zandieh; Alexander G Nagy; Audrey Spielmann; William C Yee; Alan A Weiss; Eric M Yoshida (Canadian Journal of Gastroenterology)
A case of a 60-year-old man with recurrent rectal villous adenoma is described. Preoperative staging with endoscopic ultrasound (EUS) and magnetic resonance imaging (MRI) revealed very discordant results. EUS showed a tumour present in the mucosa with no submucosal invasion, while MRI revealed invasion of the muscularis propria consistent with an invasive stage T2 carcinoma. Based on the MRI findings, the patient underwent a low anterior resection of the tumour. The surgical pathology specimen revealed a villous adenoma with low-grade dysplasia but no carcinoma and no extension into the muscularis propria. The present case highlights the uncertainty that currently exists as to which imaging modality provides the greatest accuracy in the staging of rectal cancer and in guiding the type of surgical procedure performed. Two recent meta-analyses and a systematic review of the literature point to EUS as the imaging modality of choice for determining muscularis propria and perirectal tissue invasion, as well as nodal involvement.